Promotion Cost Analysis at Inspiration Point Coworking Space Karawang - Nurul Fadillah; Dedi Mulyadi; Santi Pertiwi Hari Sandi (International Journal of Economics and Management Research, 2025)
Promotion is one of the important strategies in increasing business competitiveness, especially in the growing coworking space industry. The purpose of this study is to determine, analyze, calculate and explain (1) how promotional activities are carried out, (2) how much income is obtained from promotions carried out at MSMES Titik Inspirasi coworking space Karawang. The method used is a qualitative descriptive technique using data collection, interviews and literature studies related to the research variables. The results of the study show that the promotional strategy provides results on income each month. December recorded the highest income of IDR 35,421,000. On the other hand, April experienced a significant decline with an income of only IDR 174,000. Overall, the total promotional costs incurred during 2024 reached IDR 71,694,000 with a frequency of 7-9 promotional activities each month. It can be concluded that the digital promotion strategy through Instagram, sponsorship to expand market reach, and various offline activities such as workshops, training classes, and open tables in events and discount programs at certain moments have a positive impact on increasing income.